High-toughness PVC composite material and application thereof in corrugated soft leather
By adding components such as phosphobenzoxazine-based nano-silica to PVC materials, combined with high-speed stirring and hot pressing forming processes, the problems of insufficient impact resistance and heat resistance of PVC materials are solved, and its toughness is significantly improved and Flame retardant performance extends the scope of application.
Patent Information
- Application Number
- CN202411734554.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The impact resistance, heat resistance and flame retardant properties of existing PVC materials are insufficient, which limits the widening of their application range.
Using phosphobenzoxazine-based nanosilica, lead stearate, calcium stearate and other components combined with PVC, high-toughness PVC composite materials are prepared through high-speed stirring and hot pressing forming processes to enhance their Mechanical properties, heat resistance and flame retardant properties.
It significantly improves the toughness, heat resistance and flame retardant properties of PVC composites, enhances its performance under impact and heat treatment, and expands its application range.
Smart Images

Figure CN119220034A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of PVC, in particular to a high-toughness PVC composite material and application thereof in corrugated soft leather. Background Art
[0002] Polyvinyl chloride (PVC) is a general-purpose resin with large output and excellent comprehensive performance. Due to the large-scale promotion and use of chemical building materials, the proportion of PVC hard products has been increasing, especially in the fields of pipes, plates, sheets, soft or hard pipes, etc. Therefore, the demand for chemical building materials has increased rapidly. It is of great significance to require high-toughness PVC composite materials to adapt to the healthy and stable development of chemical building materials. However, the use of polyvinyl chloride resin as a chemical building material has obvious defects, such as poor impact resistance. The notched impact strength of pure hard PVC products is only 2.2KJ / m 2 , poor heat resistance, the Vicat softening temperature of rigid PVC products is generally less than 80°C. These defects greatly limit the further expansion of the application scope of PVC materials.
[0003] Therefore, in order to improve the impact toughness of polyvinyl chloride and expand its application, researchers have conducted a lot of research. For example, the patent with application publication number CN 105623153 A discloses a nano-silicon dioxide toughened PVC corrugated pipe and its preparation method. The invention uses PVC, nano-silicon dioxide, nano-calcium carbonate, lead stearate, etc. as raw materials to prepare a material with good mechanical properties, but does not improve the flame retardant properties of PVC materials. Summary of the invention
[0004] The object of the present invention is to overcome one or more deficiencies in the prior art and to provide a high-toughness PVC composite material. The prepared PVC composite material has good toughness, flame retardancy and heat resistance.
[0005] The present invention also provides an application of the high-toughness PVC composite material in corrugated soft leather.
[0006] In order to achieve the above object, a technical solution adopted by the present invention is: A high-toughness PVC composite material, the PVC composite material comprising the following components in parts by weight: 100 parts of PVC, 0.1-5 parts of phosphorus-containing benzoxazine-based nano-silicon dioxide, 5-8 parts of tribasic lead sulfate, 0.5-1 parts of calcium stearate, 0.6-1.2 parts of lead stearate, and 0.5-1 parts of stearic acid; The preparation method of the high-toughness PVC composite material is: Tribasic lead sulfate, calcium stearate, lead stearate, stearic acid and PVC are placed in a high-speed mixer and stirred at high speed for 10 minutes. Then, phosphorus-containing benzoxazine-based nano-silica is added thereto and stirred for 5 minutes. The mixture is placed in a double-roll mill for mixing. The mixture is then placed in a flat vulcanizer at 180°C and 7.5MPa for hot pressing. Finally, the mixture is cold pressed to obtain a high-toughness PVC composite material.
[0007] In some embodiments of the present invention, the mixing temperature is 180° C. and the mixing time is 5-10 min.
[0008] In some embodiments of the present invention, the preparation method of the phosphorus-containing benzoxazine-based nano-silica is: (1) Under a nitrogen atmosphere, 5-hydroxyisophthalaldehyde and nano-silica modified by a silane coupling agent are added to a flask containing an ethanol solvent, stirred and dispersed, heated to 75-85°C, and reacted for 5-8 hours. After the reaction is completed, the mixture is filtered, washed with deionized water, and dried to obtain an intermediate 1, wherein the amount ratio of 5-hydroxyisophthalaldehyde to nano-silica modified by a silane coupling agent is (5-10) mmol:1 g; Intermediate 1 is synthesized by condensation reaction of the aldehyde group in 5-hydroxyisophthalaldehyde and the amino group in nano-silica modified by silane coupling agent. The reaction process is as follows: ,in It is nano silicon dioxide; (2) Under a nitrogen atmosphere, diethylenetriamine and intermediate 1 are added to a flask, stirred and dispersed, and then a 36% formaldehyde aqueous solution is added thereto at 65-75°C, and the temperature is raised to 90-100°C. The reaction is carried out for 2-4 hours. After the reaction is completed, vacuum dehydration is performed to obtain intermediate 2. The dosage ratio of diethylenetriamine, intermediate 1, and formaldehyde is 1 mol: (1.8-2.2) mol: (4.5-5) mol; Using diethylenetriamine, intermediate 1 and formaldehyde as raw materials, intermediate 2 is obtained through Manniene reaction. The reaction process is as follows: ; (3) Add intermediate 2 and formaldehyde to a flask filled with ethanol solvent, stir and disperse, heat to 55-65°C, react for 1-3 hours, then add dimethyl phosphite, react for 3-6 hours, after the reaction, rotary evaporate and dry to obtain phosphorus-containing benzoxazine-based nano-silica, the amount ratio of intermediate 2, formaldehyde and dimethyl phosphite is 1 mol: (1-1.2) mol: (1-1.5) mol; The secondary amine in intermediate 2 is reacted with dimethyl phosphite and formaldehyde through Manniene to prepare phosphorus-containing benzoxazine-based nano-silica. The reaction process is as follows: .
[0009] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art: (1) The present invention uses 5-hydroxyisophthalaldehyde, nano-silica modified by a silane coupling agent, diethylenetriamine, dimethyl phosphite, etc. as raw materials, and through a series of reactions, phosphorus-containing benzoxazine-based nano-silica is prepared. The preparation method is simple and the structure is novel. Then, the nano-silica is added to PVC and mixed evenly to obtain a high-toughness PVC composite material.
[0010] (2) The nano-silicon dioxide used in the present invention is an inorganic nano-particle. Due to its extremely large surface energy and a large number of dangling bonds, it is easy to agglomerate. The present invention combines it with organic matter to increase its compatibility with organic matter and reduce the degree of agglomeration. It is added to the PVC material and can be evenly dispersed in the PVC. When subjected to a tensile load, the tensile stress extends and disperses along the molecular chain arrangement of the mesh structure, thereby increasing the tensile strength. In addition, the nano-silicon dioxide rigid particles also play a role in stress concentration in the matrix. Stress concentration will cause an increase in the three-dimensional axial stress around the particles, which will cause the debonding of the interface between the particles and the matrix. This debonding will cause the generation of cavities, causing the stress state around the cavities to change and generate shear stress. This shear stress will absorb a large amount of impact energy, thereby playing a toughening role.
[0011] (3) The phosphorus-containing benzoxazine-based nano-silica prepared by the present invention not only contains heat-resistant inorganic nano-silica particles, rigid benzene ring structure and hexacyclic ring structure, but also has a benzoxazine structure. When the benzoxazine structure is heated, it can absorb heat and open the ring to cross-link to produce a huge cross-linked network structure. Adding it to PVC material can further improve the heat resistance of the material.
[0012] (4) The PVC material prepared by the present invention contains flame-retardant phosphorus, nitrogen and silicon elements, which complement each other and jointly improve the flame retardant properties of the PVC composite material. The PVC composite material prepared by the present invention has good mechanical properties, heat resistance and flame retardant properties through experiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is the impact section of Example 1. As can be seen from the figure, there are many wrinkles on the fracture surface that are pulled up during the impact fracture process, and this is a typical ductile fracture. The phosphorus-containing benzoxazine-based nano-silica has good interface bonding and good dispersion with the PVC matrix, which causes a large number of "wrinkles" to appear during the impact process, thereby improving toughness. DETAILED DESCRIPTION
[0014] The above scheme is further described below in conjunction with specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions adopted in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.
[0015] Preparation method of silane coupling agent modified nano-silica: 5g of nano-silica is activated in an oven at 120°C for 12h, 50mL of toluene solvent is added, stirred and dispersed, and then 10mL of aminopropyltriethoxysilane is added thereto, and refluxed at 120°C for 60h. After the reaction is completed, it is washed with toluene and dried to obtain nano-silica modified by silane coupling agent. Embodiment 1
[0016] (1) Under a nitrogen atmosphere, 50 mmol of 5-hydroxyisophthalaldehyde and 10 g of nano-silica modified by a silane coupling agent were added to a flask containing an ethanol solvent, stirred and dispersed, and the temperature was raised to 80°C. The reaction was carried out for 6 h. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried to obtain an intermediate 1.
[0017] (2) Under a nitrogen atmosphere, 0.1 mol of diethylenetriamine and 0.18 mol of intermediate 1 were added to a flask and stirred for dispersion. A 36% (mass fraction) formaldehyde aqueous solution was added at 60°C, and the molar amount of formaldehyde was 0.48 mol. The temperature was raised to 95°C and the reaction was carried out for 3 h. After the reaction was completed, vacuum dehydration was performed to obtain intermediate 2.
[0018] (3) 0.2 mol of intermediate 2 and 0.24 mol of formaldehyde were added to a flask containing ethanol solvent, stirred and dispersed, heated to 55°C, and reacted for 2 h. Then 0.25 mol of dimethyl phosphite was added thereto and reacted for 4 h. After the reaction was completed, the mixture was rotary evaporated and dried to obtain phosphorus-containing benzoxazine-based nano-silica.
[0019] (4) 7 g of tribasic lead sulfate, 0.8 g of calcium stearate, 1 g of lead stearate, 0.5 g of stearic acid, and 100 g of PVC were placed in a high-speed mixer and stirred at high speed for 10 min. Then, 0.1 g of phosphorus-containing benzoxazine-based nano-silica was added and stirred for 5 min. The mixture was placed in a double-roll mill for mixing. The mixture was then placed in a flat vulcanizer at 180°C and 7.5 MPa for hot pressing. Finally, the mixture was cold pressed to obtain a high-toughness PVC composite material. Embodiment 2
[0020] (1) Under a nitrogen atmosphere, 80 mmol of 5-hydroxyisophthalaldehyde and 10 g of nano-silica modified by a silane coupling agent were added to a flask containing an ethanol solvent, stirred and dispersed, and the temperature was raised to 75°C for reaction for 8 h. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried to obtain an intermediate 1.
[0021] (2) Under a nitrogen atmosphere, 0.1 mol of diethylenetriamine and 0.2 mol of intermediate 1 were added to a flask and stirred for dispersion. A 36% (mass fraction) formaldehyde aqueous solution was added at 70°C, and the molar amount of formaldehyde was 0.45 mol. The temperature was raised to 100°C and the reaction was carried out for 3 h. After the reaction was completed, vacuum dehydration was performed to obtain intermediate 2.
[0022] (3) 0.2 mol of intermediate 2 and 0.2 mol of formaldehyde were added to a flask containing ethanol solvent, stirred and dispersed, heated to 60°C, and reacted for 2 h. Then 0.25 mol of dimethyl phosphite was added thereto and reacted for 4 h. After the reaction was completed, the mixture was rotary evaporated and dried to obtain phosphorus-containing benzoxazine-based nano-silica.
[0023] (4) 6 g of tribasic lead sulfate, 0.6 g of calcium stearate, 0.8 g of lead stearate, 0.9 g of stearic acid, and 100 g of PVC were placed in a high-speed mixer and stirred at high speed for 10 min. Then, 2 g of phosphorus-containing benzoxazine-based nano-silica was added and stirred for 5 min. The mixture was placed in a double-roll mill for mixing. The mixture was then placed in a flat vulcanizer at 180°C and 7.5 MPa for hot pressing. Finally, the mixture was cold pressed to obtain a high-toughness PVC composite material. Embodiment 3
[0024] (1) Under a nitrogen atmosphere, 100 mmol of 5-hydroxyisophthalaldehyde and 10 g of nano-silica modified by a silane coupling agent were added to a flask containing an ethanol solvent, stirred and dispersed, and the temperature was raised to 85°C. The reaction was carried out for 5 h. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried to obtain an intermediate 1.
[0025] (2) Under a nitrogen atmosphere, 0.1 mol of diethylenetriamine and 0.22 mol of intermediate 1 were added to a flask and stirred for dispersion. A 36% (mass fraction) formaldehyde aqueous solution was added at 70°C, and the molar amount of formaldehyde was 0.45 mol. The temperature was raised to 100°C and the reaction was carried out for 3 h. After the reaction was completed, vacuum dehydration was performed to obtain intermediate 2.
[0026] (3) 0.2 mol of intermediate 2 and 0.2 mol of formaldehyde were added to a flask containing ethanol solvent, stirred and dispersed, heated to 65°C, and reacted for 1 hour. Then 0.2 mol of dimethyl phosphite was added thereto and reacted for 6 hours. After the reaction was completed, the mixture was rotary evaporated and dried to obtain phosphorus-containing benzoxazine-based nano-silica.
[0027] (4) 6 g of tribasic lead sulfate, 0.5 g of calcium stearate, 0.6 g of lead stearate, 1 g of stearic acid, and 100 g of PVC were placed in a high-speed mixer and stirred at high speed for 10 min. Then, 3 g of phosphorus-containing benzoxazine-based nano-silica was added and stirred for 5 min. The mixture was placed in a double-roll mill for mixing. The mixture was then placed in a flat vulcanizer at 180°C and 7.5 MPa for hot pressing. Finally, the mixture was cold pressed to obtain a high-toughness PVC composite material. Embodiment 4
[0028] (1) Under a nitrogen atmosphere, 80 mmol of 5-hydroxyisophthalaldehyde and 10 g of nano-silica modified by a silane coupling agent were added to a flask containing an ethanol solvent, stirred and dispersed, and the temperature was raised to 85°C. The reaction was carried out for 6 h. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried to obtain an intermediate 1.
[0029] (2) Under a nitrogen atmosphere, 0.1 mol of diethylenetriamine and 0.19 mol of intermediate 1 were added to a flask and stirred for dispersion. A 36% (mass fraction) formaldehyde aqueous solution was added at 75°C, and the molar amount of formaldehyde was 0.45 mol. The temperature was raised to 95°C and the reaction was carried out for 4 h. After the reaction was completed, vacuum dehydration was performed to obtain intermediate 2.
[0030] (3) 0.2 mol of intermediate 2 and 0.22 mol of formaldehyde were added to a flask containing ethanol solvent, stirred and dispersed, heated to 60°C, and reacted for 3 h. Then 0.25 mol of dimethyl phosphite was added thereto and reacted for 3 h. After the reaction was completed, the mixture was rotary evaporated and dried to obtain phosphorus-containing benzoxazine-based nano-silica.
[0031] (4) 5 g of tribasic lead sulfate, 1 g of calcium stearate, 1.2 g of lead stearate, 0.5 g of stearic acid, and 100 g of PVC were placed in a high-speed mixer and stirred at high speed for 10 min. Then, 4 g of phosphorus-containing benzoxazine-based nano-silica was added and stirred for 5 min. The mixture was placed in a double-roll mill for mixing. The mixture was then placed in a flat vulcanizer at 180°C and 7.5 MPa for hot pressing. Finally, the mixture was cold pressed to obtain a high-toughness PVC composite material. Embodiment 5
[0032] (1) Under a nitrogen atmosphere, 100 mmol of 5-hydroxyisophthalaldehyde and 10 g of nano-silica modified by a silane coupling agent were added to a flask containing an ethanol solvent, stirred and dispersed, and the temperature was raised to 75°C. The reaction was carried out for 7 h. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried to obtain an intermediate 1.
[0033] (2) Under a nitrogen atmosphere, 0.1 mol of diethylenetriamine and 0.22 mol of intermediate 1 were added to a flask and stirred for dispersion. A 36% (mass fraction) formaldehyde aqueous solution was added at 65°C, and the molar amount of formaldehyde was 0.5 mol. The temperature was raised to 90°C and the reaction was carried out for 2 h. After the reaction was completed, vacuum dehydration was performed to obtain intermediate 2.
[0034] (3) 0.2 mol of intermediate 2 and 0.24 mol of formaldehyde were added to a flask containing ethanol solvent, stirred and dispersed, heated to 55°C, and reacted for 2 h. Then 0.3 mol of dimethyl phosphite was added thereto and reacted for 5 h. After the reaction was completed, the mixture was rotary evaporated and dried to obtain phosphorus-containing benzoxazine-based nano-silica.
[0035] (4) 8 g of tribasic lead sulfate, 1 g of calcium stearate, 1 g of lead stearate, 1 g of stearic acid, and 100 g of PVC were placed in a high-speed mixer and stirred at high speed for 10 min. Then, 5 g of phosphorus-containing benzoxazine-based nano-silica was added and stirred for 5 min. The mixture was placed in a double-roll mill for mixing. The mixture was then placed in a flat vulcanizer at 180°C and 7.5 MPa for hot pressing. Finally, the mixture was cold pressed to obtain a high-toughness PVC composite material.
[0036] Comparative Example 1 The difference between this comparative example and Example 1 is that in step (4), nano-silica is used instead of phosphorus-containing benzoxazine-based nano-silica.
[0037] The tensile properties were tested using an electronic universal testing machine at a tensile speed of 20 mm / min.
[0038] A simply supported beam impact testing machine was used to carry out a “V” notch impact test.
[0039] Table 1: Tensile strength (MPa) <![CDATA[Impact strength (kJ / m 2 )]]> Example 1 48.64 3.98 Example 2 52.15 5.04 Example 3 56.80 5.92 Example 4 55.43 6.50 Example 5 53.08 5.74 Comparative Example 1 43.89 2.96 It can be seen from the table that the PVC composite material prepared by the present invention has good tensile strength and impact strength. The greater the impact strength, the stronger the toughness. Therefore, the material prepared by the present invention has higher toughness.
[0040] The Vicat softening point was tested using a heat deformation Vicat temperature tester. Under a load of 49.5N, the heating rate was 50℃ / h and the thickness was 1mm. 2 The temperature at which the indenter is pressed into the cavity by 100 μm.
[0041] Table 2:
[0042] It can be seen from the table that the PVC composite material prepared by the present invention has good heat resistance.
[0043] The flame retardant properties of PVC composites were tested using an oxygen index tester.
[0044] Table 3: LOI (%) Example 1 29.4 Example 2 31.2 Example 3 32.8 Example 4 33.4 Example 5 34.0 Comparative Example 1 25.8 It can be seen from the table that the PVC composite material prepared by the present invention has good flame retardant properties.
[0045] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
Claims
1. A high-toughness PVC composite material, characterized in that: The PVC composite material comprises the following components in parts by weight: 100 parts of PVC, 0.1-5 parts of phosphorus-containing benzoxazine-based nano-silicon dioxide, 5-8 parts of tribasic lead sulfate, 0.5-1 parts of calcium stearate, 0.6-1.2 parts of lead stearate, and 0.5-1 parts of stearic acid; The preparation method of the high-toughness PVC composite material is: Tribasic lead sulfate, calcium stearate, lead stearate, stearic acid and PVC are placed in a high-speed mixer and stirred at high speed for 10 minutes. Then, phosphorus-containing benzoxazine-based nano-silica is added thereto and stirred for 5 minutes. The mixture is placed in a double-roll mill for mixing. The mixture is then placed in a flat vulcanizer at 180°C and 7.5MPa for hot pressing. Finally, the mixture is cold pressed to obtain a high-toughness PVC composite material.
2. The high-toughness PVC composite material according to claim 1, characterized in that: The mixing temperature is 180° C., and the mixing time is 5-10 minutes.
3. The high-toughness PVC composite material according to claim 1, characterized in that: The preparation method of the phosphorus-containing benzoxazine-based nano-silica is as follows: (1) Under a nitrogen atmosphere, 5-hydroxyisophthalaldehyde and nano-silica modified with a silane coupling agent were added to a flask containing an ethanol solvent, stirred and dispersed, heated to 75-85°C, and reacted for 5-8 hours. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried to obtain an intermediate 1; (2) Under a nitrogen atmosphere, diethylenetriamine and intermediate 1 are added to a flask, stirred and dispersed, and then a 36% formaldehyde aqueous solution is added thereto at 65-75°C, and the temperature is raised to 90-100°C, and the reaction is carried out for 2-4 hours. After the reaction is completed, vacuum dehydration is performed to obtain intermediate 2; (3) Add intermediate 2 and formaldehyde into a flask containing ethanol solvent, stir and disperse, heat to 55-65°C, react for 1-3 hours, then add dimethyl phosphite, react for 3-6 hours. After the reaction is completed, rotary evaporate and dry to obtain phosphorus-containing benzoxazine-based nano-silica.
4. The high-toughness PVC composite material according to claim 3, characterized in that: In the above (1), the usage ratio of 5-hydroxyisophthalaldehyde and nano-silica modified by silane coupling agent is (5-10) mmol:1g.
5. The high-toughness PVC composite material according to claim 3, characterized in that: In the above (2), the usage ratio of diethylenetriamine, intermediate 1 and formaldehyde is 1 mol: (1.8-2.2) mol: (4.5-5) mol.
6. The high-toughness PVC composite material according to claim 3, characterized in that: In the above (3), the usage ratio of the intermediate 2, formaldehyde and dimethyl phosphite is 1 mol: (1-1.2) mol: (1-1.5) mol.
7. Use of the high-toughness PVC composite material according to any one of claims 1 to 6 in corrugated soft leather.
Citation Information
Patent Citations
Nano-silicon dioxide toughened PVC (polyvinyl chloride) corrugated pipe and preparation method therefor
CN105623153A
Nano silicon dioxide and phosphorus flame retardant compounded modified waterborne polyurethane and preparation method thereof
CN111434701A
Preparation method and application of aminated nano silicon dioxide
CN116836454A
Preparation method of nano silicon dioxide composite flame retardant modified polystyrene
CN117964984A
High-temperature-resistant PVC (polyvinyl chloride) material and preparation method thereof
CN118546482A
Cited By
Preparation method of nano silicon dioxide modified polyurethane thermal insulation material
CN120923718A
